Baroreflex sensitivity, blood pressure buffering, and resonance: what are the links? Computer simulation of healthy subjects and heart failure patients - van de Vooren, Hedde; Gademan, Maaike G J; Swenne, Cees A; TenVoorde, Ben J; Schalij, Martin J; Van der Wall, Ernst E (Journal of applied physiology (1985), 2007)
The arterial baroreflex buffers slow (<0.05 Hz) blood pressure (BP) fluctuations, mainly by controlling peripheral resistance. Baroreflex sensitivity (BRS), an important characteristic of baroreflex control, is often noninvasively assessed by relating heart rate (HR) fluctuations to BP fluctuations; more specifically, spectral BRS assessment techniques focus on the BP-to-HR transfer function around 0.1 Hz. Skepticism about the relevance of BRS to characterize baroreflex-mediated BP buffering is based on two considerations: 1) baroreflex-modulated peripheral vasomotor function is not necessarily related to baroreflex-HR transfer; and 2) although BP fluctuations around 0.1 Hz (Mayer waves) might be related to baroreflex BP buffering, they are merely a not-intended side effect of a closed-loop control system. To further investigate the relationship between BRS and baroreflex-mediated BP buffering, we set up a computer model of baroreflex BP control to simulate normal subjects and heart failure patients. Output variables for various randomly chosen combinations of feedback gains in the baroreflex arms were BP resonance, BP-buffering capacity, and BRS. Our results show that BP buffering and BP resonance are related expressions of baroreflex BP control and depend strongly on the sympathetic gain to the peripheral resistance. BRS is almost uniquely determined by the vagal baroreflex gain to the sinus node. In conclusion, BP buffering and BRS are unrelated unless coupled gains in all baroreflex limbs are assumed. Hence, the clinical benefit of a high BRS is most likely to be attributed to vagal effects on the heart instead of to effective BP buffering.